Intermittent exposure to traces of green leaf volatiles triggers the production of (Z)-3-hexen-1-yl acetate and (Z)-3-hexen-1-ol in exposed plants - Ozawa, Rika (Landes Bioscience, 2013)
Intermittent exposure during a period of 3 weeks of undamaged Arabidopsis plants to trace amounts of volatiles emitted by freshly damaged Arabidopsis plants resulted in an increase of subsequent artificial-damage-induced production of (Z)-3-hexen-1-yl acetate and (Z)-3-hexen-1-ol in the exposed Arabidopsis plants when compared with Arabidopsis plants exposed to undamaged Arabidopsis plant volatiles (control plants). We previously showed that (Z)-3-hexen-1-yl acetate attracts a parasitic wasp, Cotesia glomerata. Thus, the induced production of this volatile explained our previously reported finding that, when artificially damaged, the exposed plants were more attractive to C. glomerata than control plants.